On the role of graphene oxide in bifunctional Ni/MOF/rGO composites in electrochemical nitrate detection and oxygen evolution reaction. (8th December 2022) - Pasarakonda, Satya Lakshmi; Ponnada, Srikanth; Gorle, Demudu Babu; Chandra Bose, Rapaka S.; Palariya, Anjali; Kiai, Maryam Sadat; Gandham, Hima Bindu; Kathiresan, Murugavel; Sharma, Rakesh K; Nowduri, Annapurna
Abstract : Bi-functional metal organic frameworks as promising porous framework hybrid materials for electrochemical nitrate sensing and oxygen evolution reaction. Abstract : Metal–organic frameworks as promising porous hybrid materials have been widely used in electrocatalytic applications. Most MOFs' poor electron-conductive and low stability properties would exclude them from being used as electrocatalysts. To overcome these difficulties, in this study, both Ni-MOF and reduced graphene oxide (Ni-MOF/rGO) composites are synthesized by using a simple facile method. The composite modified electrode possesses higher bifunctional catalytic activity for the electrochemical sensing of nitrate and oxygen evolution reaction. The composite was characterized using different analytical techniques such as FTIR, Raman, XRD, SEM, TEM, and XPS analysis. The electrochemical properties of the composite materials were investigated by using electroanalytical techniques in detail. The Ni-MOF/rGO composite modified electrode shows substantial sensitivity (0.08 μA μM −1 cm −2 ), a wider linear range (5–10 μM), and a lower detection limit (4.018 μM). Further, the Ni-MOF/rGO composite showed superior OER activity with a low overpotential (90 mV) and a small Tafel slope (107 mV dec −1 ).